Primary aortoduodenal fistula - George St. Stoyanov; Deyan Dzhenkov; Lilyana Petkova (University of São Paulo, 2021)
Aortoduodenal fistula (ADF) is the most common type of aortoenteric fistula (AEF). This is a rare entity, which produces communication between an abdominal aortic aneurysm (AAA) and the gastrointestinal tract (GIT), resulting in massive gastrointestinal bleeding. AEF/ADF is difficult to recognize clinically, with the classical triad of symptoms including a pulsating, palpable mass, abdominal pain, and GIT bleeding. AEF/ADF can be classified into primary when a communication between an AAA and the GIT develops with no history of prior aortic reconstructive surgery, and secondary, where the communication is on the background of previous aortic reconstructive surgery. Herein we present a case report of a 75-year-old Caucasian male patient with a clinical history of AAA, who presented with massive GIT bleeding and expired shortly after. An autopsy revealed communication between an atherosclerotic AAA and the lower third of the duodenum.